A Cross‐Disciplinary Examination of Firm Orientations' Performance Outcomes: The Role of Supply Chain Flexibility. Issue 4 (22nd November 2014) - Gligor, David M.
<x xml:space="preserve">Abstract</x> Although market orientation (MO) has long been considered an important business philosophy, the examination of MO outside the firm's boundaries has been rather limited. To address this, this study explores how supply chain orientation and operational flexibility (FLX) facilitate the implementation of MO. Although the positive impact of MO on firm performance has been well established, this study highlights that such benefits are enhanced by the development of supply chain related capabilities. Results indicate that market‐oriented firms are more likely to realize the strategic importance of managing the supply chain when operating under conditions of high environmental munificence, dynamism, and complexity. This provides a better understanding of the complex relationship between the demand and supply sides of the firm. This study highlights the importance of marketing theory and concepts to supply chain management scholars, and vice versa. This further accentuates the importance of eliminating the disconnect between supply and demand‐management processes, also described as the "Great Divide" (Drucker 1973; Esper et al. 2010a, b). A number of key managerial implications are offered as well.